PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK SULUTGO KANTOR PUSAT - Suprejo, Nanda Dewi Zafitri; Djawa, Djibrael (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2023)
The issues raised in writing this thesis are How Work Motivation on Employee Performance at PT. Bank Sulut Go, while the purpose of this study was to analyze "The Influence of Work Motivation on Employee Performance at PT. Bank Sulut Manado Headquarters Manadoâ€ This type of research is quantitative research and the research method uses descriptive research methods. The population is 35 employees and the sample is 35 employees. The analysis used inthis research is simple regression analysis and correlation. The results of the research by calculating the correlation coefficient of 0.740, this illustrates the regression equation between the variables of work motivation on employee performance Y = 0.095 + 0.967 which is in the strong category which shows the relationship between work motivation variables and employee performance variables at PT. Bank Sulut Go Manado Head Office is very strong. The t testshows t-count of (6.316) > t-table (2.034) meaning that Ha is accepted, namely that there is a relationship between work motivation variables and employee performance at PT. Bank Sulut Go Headquarters Manado. From the analysis results show that the performance of employees at PT. Bank Sulut Go Manado Head Office is categorized as quite good and still needs to be improved. Good Employee Work Motivation will be able to improve Employee Performance atPT. Bank Sulut Go Manado Head Office